We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
109
1
avatar

What is the derivative of f(x)=3^(5x^2-4x). I'm shown that the answer is f'(x)=2ln3(5x-2)(3^(5x^2-4x)) but I'm not sure where the 2 in the front is coming from. Instead of 5x-2 shouldnt it also be 10x-4?

 Nov 24, 2018

Best Answer 

 #1
avatar+4779 
+1

\(f(x) = 3^{5x^2-4x} = e^{\ln(3)(5x^2-4x)}\)

 

\(\dfrac{d}{dx} g(f(x)) = g^\prime(f(x))f^\prime(x) \\ \text{here we have}\\ g(x) = e^x \\ f(x) = \ln(3)(5x^2-4x)\)

 

\(\dfrac{d}{dx}e^x = e^x \text{ so }\\ g^\prime(f(x)) = e^{\ln(3)(5x^2-4x)} \\ f^\prime(x) = \ln(3)(10x-4) \text{ so }\\ g^\prime(f(x)) f^\prime(x) = e^{\ln(3)(5x^2-4x)}\cdot \ln(3)(10x-4) = \\ 2\ln(3)(5x-2)e^{\ln(3)(5x^2-4x)} = \\ 2\ln(3)(5x-2)3^{5x^2-4x}\)

 

ugh.. I posted all that when all I had to say was that 

 

2(5x-2) = 10x - 4

.
 Nov 24, 2018
edited by Rom  Nov 24, 2018
edited by Rom  Nov 24, 2018
 #1
avatar+4779 
+1
Best Answer

\(f(x) = 3^{5x^2-4x} = e^{\ln(3)(5x^2-4x)}\)

 

\(\dfrac{d}{dx} g(f(x)) = g^\prime(f(x))f^\prime(x) \\ \text{here we have}\\ g(x) = e^x \\ f(x) = \ln(3)(5x^2-4x)\)

 

\(\dfrac{d}{dx}e^x = e^x \text{ so }\\ g^\prime(f(x)) = e^{\ln(3)(5x^2-4x)} \\ f^\prime(x) = \ln(3)(10x-4) \text{ so }\\ g^\prime(f(x)) f^\prime(x) = e^{\ln(3)(5x^2-4x)}\cdot \ln(3)(10x-4) = \\ 2\ln(3)(5x-2)e^{\ln(3)(5x^2-4x)} = \\ 2\ln(3)(5x-2)3^{5x^2-4x}\)

 

ugh.. I posted all that when all I had to say was that 

 

2(5x-2) = 10x - 4

Rom Nov 24, 2018
edited by Rom  Nov 24, 2018
edited by Rom  Nov 24, 2018

14 Online Users

avatar
avatar